Strategy Alternatives to Increase Capacity: Study Case in PT Turmerica, an Herbal Extract Manufacturer - Haikal Sofyan Arif; Desy Anisya Farmaciawaty (Eduvest - Journal of Universal Studies, 2025)
The increased global demand for herbal extracts has made PT Turmerica need to re-evaluate its current output capacity. This study aimed to evaluate the most feasible and profitable business solution to solve the production capacity gap and meet the market demand through a combination of technical and financial analyses. Using the TELOS framework and Decision Tree Analysis, three strategic alternatives have been evaluated for consideration: A1 is to invest in a new concentrator machine; A2 is outsourcing; and A3 is extending working hours. From production data from 2023–2025 and expected market growth rates, it can be seen that the current production capacity of 161,915 kg/year is insufficient to meet future demand; the gap to be bridged is estimated to exceed 17% by 2027. The analysis found that the extractor machine was the main bottleneck in the extraction line, lowering throughput and increasing cleaning and maintenance time. A1 (investment in a new concentrator machine) is the most beneficial alternative, improving capacity by 35.1% as it speeds up extraction concentration, makes extract thickening unnecessary for the extractor, and prevents blockages. In contrast, both A2 (outsourcing) and A3 (additional working hours) have only increased capacity by 8.6% and 24.6%, respectively, with much higher operational risks and weaker long-term sustainability. Based on TELOS results, A1 offers the most feasible and profitable option according to decision tree analysis, which produces higher cash flow.